El ms. 212 de la BUV i les cròniques de Joan I, Martí l'Humà i Ferran I - Escartí, Vicent Josep (Caplletra. Revista Internacional de Filologia, 2015)
As indicated by the title, this is an edition of the three Chronicles mentioned above, prepared on the basis of a ms. extant in the Library of the University of Valencia not taken into account in the previous, very limited, edition by Frederic P. Verrié (1950 i 1951), of the Chronicles of Joan I and Martí l'Humà. The present editor relates the text he publishes to the context of the Valentian ms.